1944. The Canadians in Normandy - Dorning, W.A. (Scientia Militaria - South African Journal of Military Studies, 2011)
The story of the Allied invasion of France in June 1944 has been told in countless military-history books. Previous publications on the Allied invasion and the subsequent Normandy campaign have, however, tended to concentrate on the British and American role in the fighting, while the Canadian contribution has received scant attention. This in itself is surprising, as the Canadians played a far from peripheral role in the invasion and the campaign which followed in the hinterland of Normandy. The Canadians eventually fielded an entire Army under own Command (the First Canadian Army) comprising nearly 100000 troops in the Normandy campaign, and they were frequently allocated a central and crucial role in the overall Allied strategy by the Supreme Commander of the Allied Forces in France, Gen Montgomery. Indeed, on more than one occasion, the Canadian contribution was decisive to the successful achievement of the Allied strategy.